Analisis Pendidikan Pondok Pesantren Purbaganal Sosopan bagi Masyarakat Kabupaten Padang Lawas Utara - Yunita Partiwi; Muhammad Adika Nugraha; Pulung Sumantri; Latifah Hanum; Muhammad Ricky Hardiyansyah; Ridho Gilang Amalsyah Saragih (Universitas Islam Sumatera Utara, 2022)
This research aims to describe the role of Purbaganal Socopan Islamic Boarding School education for the people of Padang Bolak District, North Padang Lawas Regency, starting from the history of the Islamic Boarding School to the inhibiting factors in the development of this educational institution. The method used by the author in this research is a historical research method using historical methods, by conducting direct observations in the field and interviews. The results of this research describe the history of Islamic boarding schools starting from the Kingdom period, the colonial period, the period before independence to the period after independence. After that, we discuss the history of the Purbaganal Islamic Boarding School, Politeness for the Community of Padang Bolak District, North Padang Lawas Regency, the educational role of the Purbaganal Islamic Boarding School for the Community of Padang Bolak District, North Padang Lawas Regency. The initial aim of establishing this Islamic Boarding School was to bring together young people from Sosopan Village to get to know the school and get a diploma to get job opportunities. The development of this Islamic boarding school is growing very rapidly because the people in Sosopan village have quite good enthusiasm for the establishment of this Islamic boarding school. The obstacles that occur in developing this Islamic boarding school are the lack of educational facilities, differences of opinion between boarding school administrators, funding factors and a lack of teaching staff.